Tanggap Parasitoid Braconidae (Hymenoptera) Terhadap Hama Invasif Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) pada Tanaman Sayuran dan Hias di Bali - TIA GUNAWAN SARI; A. A. AYU AGUNG SRI SUNARI; I WAYAN SUPARTHA (Agrotrop : Journal on Agriculture Science, 2022)
Response of Braconid Parasitoid Against Invasive Pest, Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) on Vegetable and Ornamental Crops in Bali. Research on the respopnse of Braconid parasitoids to the invasive pest, Liriomyza trifolii that attacks ornamental plants and vegetables in Bali, was carried out from September 2020 to March 2021. This study aimed to determine the type and abundance of parasitoid populations that responded to Liriomyza trifolii on host plants in the field. In addition, this study also aims to evaluate the level of parasitization of each parasitoid against L. trifolii. This study used a purposive sampling method by taking leaf samples that showed active symptoms of Liriomyza larvae in the leaves of plants. The research focused on vegetables and ornamental plants cultivated in lowlands <500 meters above sea level (masl), mediumlands 500-1000 meters above sea level and highlands> 1000 meters above sea level. The results showed that there were two species of Braconid parasitoids that responded to Liriomyza trifolii in the field, namely Opius dissitus and Opius cromatomiyae. The relative abundance and degree of parasitization of the two parasitoids showed variation between host plant species and altitude. The relative abundance of O. dissituse was high in chrysanthemum (10.81%) at an altitude of >1000 masl and low in long beans (0.53%) at an altitude of <500 masl. The highest relative abundance of O. cromatomiyae was in marigold flowers (51.18%) at an altitude of <500 masl and the lowest was in chrysanthemum (44.83%) at an altitude of > 1000 masl. The highest level of parasitization of O. dissitus was found in pakcoy plants (50.00%) at an altitude of >1000 masl and the lowest was in mustard plants (6.06%) at an altitude of <500 masl. The highest level of parasitization of O. cromatomiyae was in celery (33.33%) at an altitude <500 masl and the lowest was in tomato plants (25.00%) at an altitude> 1000 masl. Both species of Braconid parasitoids have high potential as biological control agents for L. trifolii as indicated by their relative abundance and high levels of parasitization against these invasive pests.